Construction Considerations for Low-Cost Earth Brick Shells - Bradley, Ryan Anthony; Gohnert, Mitchell; Bulovic, Ivanka (Penerbit Universiti Sains Malaysia, 2018)
Earthen shells are typically designed as pure-compression structures; however, some issues associated with construction practice, fxity, and certain actions (i.e., loading), which induce tensile stress, are often overlooked. Thus, cracking is not uncommon in unreinforced earthen shells. Cracking is particularly undesirable in these shells due to issues associated with the durability of earthen building materials. Moisture, in particular, may signifcantly compromise the strength and longevity of earthen masonry. In this paper, conventional and contemporary techniques utilised for the construction of earthen shells are reviewed. Furthermore, construction concerns with several methodologies are identifed based on case study investigations and lessons learnt from several shells designed, built and monitored by the authors. An important fnding is that fxity generated during construction with formwork can lead to signifcant cracking in earthen shells